Commentary: The Nexus of Poverty, Hunger, and Homelessness in New Mexico - Page-Reeves, Janet (Social justice, 2011)
The author reflects on trends of poverty, hunger, and homelessness in New Mexico. According to the author, the mass media and common misconceptions promote inaccurate perceptions of poverty as well as the causes of hunger and homelessness. She argues that a lack of critical social literacy has caused the public to misunderstand the social, political, and economic aspects of poverty. The work of advocacy groups in New Mexico is also discussed.